miR-146a Plasma Levels Are Not Altered in Alzheimer’s Disease but Correlate With Age and Illness Severity - Maffioletti, Elisabetta; Milanesi, Elena; Ansari, Abulaish; Zanetti, Orazio; Galluzzi, Samantha; Geroldi, Cristina; Gennarelli, Massimo; Bocchio-Chiavetto, Luisella (Frontiers in Aging Neuroscience, 2020)
miR-146a is a microRNA involved in neuroinflammation and ageing; alterations in its expression were described in Alzheimer's disease (AD). However, most of the studies conducted so far on this miRNA included a limited number of participants and produced contradictory results. We compared miR-146a levels in plasma from 33 AD patients vs. 28 age-matched non-affected CTRL through qRT-PCR. No difference between the case and the control group was evidenced, but a correlation was detected between miR-146a levels and subjects' age (p<0.001), as well as between miR-146a levels and patients' MMSE scores (p=0.011), supporting a role for this microRNA in ageing processes and disease progression.